Evaluation of electrochromic windows impact in the energy performance of buildings in Mediterranean climates - Tavares, P. F. (2014)
Old buildings refurbishment is essential for the global improvement of building energy indicators. Within this context, the paper focuses on the energy savings that may occur when using electrochromic (EC) windows, an interesting emerging technology alternative to shading devices to control solar gain in buildings located in Mediterranean climates. The EC windows technology is briefly presented and the optical properties adjustments of the glasses are discussed according to the operated range. The EC window dynamic behavior and the different control strategies are modeled and implemented in the ESP-r building simulation program. The EC window impact in the energy needs for heating and cooling is studied, considering different ambient parameters (exterior dry bulb temperature, interior dry bulb temperature and incident radiation) and set points for the EC control. A comparison of several windows solutions (single, double-glazing and EC windows), the type of building, internal gains from occupancy, lighting and equipment and the orientation of windows are considered for discussion through the analysis of the energy needs for heating and cooling. It is concluded that for this climate the best positive results are obtained when the EC are used in the west façade. For the south façade the results show no significant advantages in using EC windows.